ANALISIS KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGANAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN BERAU - Djupiansyah Ganie; Isroiyah Isroiyah; Dawami Buchori (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2021)
The purpose of this research was to identify and clearly describe the performance of the Regional Disaster Management Agency (BPBD) employeesin handling forest and land firesin Berau Regency. The primary data source isin the form of questionnaire data which is distributed to 64 BPBD employees of Berau Regency using saturated sampling method or census. The analytical tools used include: validity and reliability tests, and weighted factor value methods.This study concludes that the results of the respondents' answers to the questionnaire regarding theperformance of BPBD employees in handling forest and land fires show varied answers, be it